Functional characterization of SCN10A variants in several cases of sudden unexplained death. (August 2019) - Gando, Ivan; Williams, Nori; Fishman, Glenn I.; Sampson, Barbara A.; Tang, Yingying; Coetzee, William A.
Highlights: Channelopathies are often associated with inherited arrhythmias and sudden death. Genetic testing can assist in determining the likely causes of sudden unexpected death. We identified five SCN10A variants in sudden unexpected death. Four of the variants led to altered Na + channel function. Abstract: Background: Multiple genome-wide association studies (GWAS) and targeted gene sequencing have identified common variants in SCN10A in cases of PR and QRS duration abnormalities, atrial fibrillation and Brugada syndrome. The New York City Office of Chief Medical Examiner has now also identified five SCN10A variants of uncertain significance in six separate cases within a cohort of 330 sudden unexplained death events. The gene product of SCN10A is the Nav1.8 sodium channel. The purpose of this study was to characterize effects of these variants on Nav1.8 channel function to provide better information for the reclassification of these variants. Methods and results: Patch clamp studies were performed to assess effects of the variants on whole-cell Nav1.8 currents. We also performed RNA-seq analysis and immunofluorescence confocal microcopy to determine Nav1.8 expression in heart. We show that four of the five rare 'variants of unknown significance' (L388M, L867F, P1102S and V1518I) are associated with altered functional phenotypes. The R756W variant behaved similar to wild-type under our experimental conditions. We failed to detect Nav1.8 protein expression in immunofluorescence microscopy in rat heart. Furthermore, RNA-seq analysis failed to detect full-length SCN10A mRNA transcripts in human ventricle or mouse specialized cardiac conduction system, suggesting that the effect of Nav1.8 on cardiac function is likely to be extra-cardiac in origin. Conclusions: We have demonstrated that four of five SCN10A variants of uncertain significance, identified in unexplained death, have deleterious effects on channel function. These data extend the genetic testing of SUD cases, but significantly more clinical evidence is needed to satisfy the criteria needed to associate these variants with the onset of SUD.